Effect of Fresh Whey in PDA on Mycelium Growth of Tricholoma crassum (Berk.) Sacc. ผลของน้ำเวย์ในอาหาร PDA ต่อการเจริญเติบโตของเส้นใยเห็ดตีนแรด - แสงเงิน คมกฤษณ์ (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2019)
The purpose of this study was to investigate growth of Tricholoma crassum (Berk.) Sacc. mycelium. The experiments were carried out in a completely randomized design (CRD) with 20 replications. Mycelia were cultured on modified PDA supplemented with potato and raw whey at 1:0 (control), 1:1, 0:2, 2:1 and 1:2 w/v per 1 liter of medium. The cultured were maintained in the dark at 28±2 ºC. After that mycelium from each PDA were transferred to sorghum seed and culture material for mushroom cultivation. It was found that control medium gave the best growth of mycelium at 4.5 cm after culture for 15 days (p < 0.05). Transferring mycelium from each PDA to sorghum seed gave the highest growth in 2:1 potato-whey supplemented PDA at 4.23 cm after culture for 15 days (p < 0.05). Growth in culture material for mushroom cultivation shown that mycelium from 1:1 potato-whey supplemented PDA gave the highest growth at 16.7 cm after culture for 35 days (p < 0.01). The results suggest that addition raw whey in PDA promoted growth of mycelium in sorghum seed and culture material for mushroom cultivation.